Acquired Mechanical Intestinal Obstruction in Children - Nuritov Nurpullo Rajabovich; Karimova Zevara Hojibayevna; Karimova Zevara Hojibayevna (Zien Journals, 2022)
CHILDREN ACQUIRED MECHANICAL INTESTINAL OBSTRUCTION. In this article the main principles of diagnosis the clinical symptoms of diseases causing vomiting syndrome of children with acquired mechanical intestinal obstruction are unified and generalized. The genera! conception of the acquired mechanical intestinal obstruction is given here. Peculiarities of clinical course and diagnostics and differential diagnostics of intussusception of intestine and adhesive obstruction of children are described in this article. Medical and diagnostic policy is proved. Authors conclude, that the earliest diagnosis of diseases which cause children acquired intestinal obstruction, decrease the quantity of complications and lethality.
Keywords: mechanical intestinal obstruction; vomiting syndrome; children; complications